VD_FINDINFO HC / 2013 / 429 vom 30. Mai 2013 - VD Tribunal cantonal (2013)
PREUVE À FUTUR, DÉCISION SUR FRAIS, DÉPENS, EXPERTISE | 255 al. 3 CPC, 255 CPC, 255a CPC, 104 al. 3 CPC (CH), 105 al. 2 CPC (CH), 106 al. 1 CPC (CH), 158 al. 1 CPC (CH), 158 al. 2 CPC (CH)